Kontribusi Nilai Curahan Kerja Wanita terhadap Pendapatan Rumah Tangga Petani Padi Sawah di Desa Noelbaki, Kecamatan Kupang Tengah, Kabupaten Kupang - Amheka, Ana Maria; Suek, Johanna; Nampa, I Wayan (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2020)
This research aims to know number of women working hours in non agricultural and agricultural sectors and their role in grain farmers’ household income. The research has carried out in Noebaki Village, using 46 samples that chosen purposively based on active women.The collected data have been analyzed descriptively. Research result shows that allocation of women working time in five activities compare to men that of eight activities. Total Women time allocation for working as many as 542 HKO (11,40 HKO/person/ in a season),Total while men time allocation as many as 1.119 HKO (24,32 HKO/person/in a season) in seedling, weeding, fertilizing, transport and post harvest activities. Besides that, women are also working in non agricultural sector as a washing cloth and weaving with working times as many as 55.71 HKO and 56,77 HKO consecutively. From this job the women can contribute as much as 1.824.627 IDR or 11.15% to the household income. This contribution is smaller compare to 50% of income. Therefore to increase the women role in economic household, they have to improve their skill in various way as individual or as a group.